Nanofat Cell Aggregates: A Nearly Constitutive Stromal Cell Inoculum for Regenerative Site-Specific Therapies. Issue 5 (November 2019) - Sesé, Borja; Sanmartín, Javier M.; Ortega, Bernat; Matas-Palau, Aina; Llull, Ramon
Abstract : Background: Recent technology developed by Tulip Medical Products allows clinicians to mechanically disaggregate fat tissue into small fat particles known as nanofat. The present study aimed to evaluate the cell yield obtained from nanofat generation in comparison to traditional methods involving enzymatic dissociation (stromal vascular fraction). Methods: Nanofat preparations were characterized by cell content and viability, based on DNA quantification and image cytometry, respectively. DNA analysis was also used to determine the cell content in unprocessed dry lipoaspirate and native adipose tissue (excised adipose tissue). To evaluate cell yield, the authors compared the number of cells recovered from 1 g of lipoaspirate between stromal vascular fraction and nanofat preparations, and subsequently determined the final cell inoculum obtained following their respective protocols. Results: The data showed that nanofat samples presented a cell burden of 7.3 million cells/g, close to 80 percent of unprocessed dry lipoaspirate, and 70 percent of native excised adipose tissue. Moreover, cell viability was not altered by mechanical disaggregation in nanofat samples compared to unprocessed dry lipoaspirate. Nanofat samples exhibited a cell yield of 6.63 million cells/g lipoaspirate, whereas stromal vascular fraction preparations resulted in only 0.68 million cells/g lipoaspirate. The final cell inoculum obtained from stromal vascular fraction isolation was 120 million cells and it required 200 to 250 cc of raw lipoaspirate as starting material, whereas nanofat preparation resulted in 125 million cells with only 20 cc of raw lipoaspirate. Conclusion: Mechanical disaggregation offers a better cell inoculum than conventional enzymatic dissociation methods by using 10 times less fat tissue as starting material and delivering a higher cell yield. Abstract : Supplemental Digital Content is available in the text.